Intergenerational Leadership and Knowledge Transfer: Case of Cobot Integration (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
This article explores the complexities and benefits of leading collaborative robots, particularly in terms of intergenerational and technological oversight. It looks at the challenges that companies face and the potential benefits that can emerge from such situations. The aim is to guide how to effectively maneuver through these different scenarios. The primary objective is to examine the hurdles that organizations must overcome, identify the available opportunities, and formulate successful strategies not only for survival but also for prosperity in this complex environment. Therefore, we support the opinion that knowledge transfer between different generations is a bidirectional process where both younger and older employees are part of knowledge sharing and knowledge receiving activities within the organization.